2017
DOI: 10.1038/s41598-017-06232-w
|View full text |Cite
|
Sign up to set email alerts
|

Hypersaline sapropels act as hotspots for microbial dark matter

Abstract: Present-day terrestrial analogue sites are crucial ground truth proxies for studying life in geochemical conditions close to those assumed to be present on early Earth or inferred to exist on other celestial bodies (e.g. Mars, Europa). Although hypersaline sapropels are border-of-life habitats with moderate occurrence, their microbiological and physicochemical characterization lags behind. Here, we study the diversity of life under low water activity by describing the prokaryotic communities from two disparate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
(49 reference statements)
1
13
1
Order By: Relevance
“…), extremely halophilic heterotrophic clostridia (Halanaerobiaceae, Halanaerobacteroidaceae, and Clostridiaceae) and spirochaetes (Spirochaetaceae) dominated among dnA metabarcodinginferred taxa. intriguingly, sequences pertaining to uncultured or unclassified bacterial divisions (e.g., oP1/Acetothermia, od1/Parcubacteria) were found at significant (1-2%) abundances in the water columns and organic-rich sediments of ursu and Fără Fund lakes (Andrei et al, 2015;2017b). to our knowledge, the transylvanian deep, hypersaline, and perennially stratified aquatic systems have no match with analogous lakes worldwide.…”
Section: Water Horizon/layer (Depth)mentioning
confidence: 81%
See 2 more Smart Citations
“…), extremely halophilic heterotrophic clostridia (Halanaerobiaceae, Halanaerobacteroidaceae, and Clostridiaceae) and spirochaetes (Spirochaetaceae) dominated among dnA metabarcodinginferred taxa. intriguingly, sequences pertaining to uncultured or unclassified bacterial divisions (e.g., oP1/Acetothermia, od1/Parcubacteria) were found at significant (1-2%) abundances in the water columns and organic-rich sediments of ursu and Fără Fund lakes (Andrei et al, 2015;2017b). to our knowledge, the transylvanian deep, hypersaline, and perennially stratified aquatic systems have no match with analogous lakes worldwide.…”
Section: Water Horizon/layer (Depth)mentioning
confidence: 81%
“…), Msbl1 candidate division, and thermoplasmata (Máthé et al, 2014;Andrei et al, 2015) N o n -c o m m e r c i a l u s e o n l y 27 Plankton diversity in transylvanian salt lakes in ursu and Fără Fund lakes, whereas reads related to uncultured archaeal divisions were detected in anaerobic layers of ursu (Parvarchaea), Fără Fund (Parvarchaea and nanohaloarchaea) (Andrei et al, 2015) and brâncoveanu (nanohaloarchaea) (Andrei et al, 2017a) lakes, respectively. Additionally, Parvarchaea was suggested as abundant component of microbial communities from hypersaline organic-rich sediments (sapropels) of ursu and Fără Fund lakes (Andrei et al, 2017b). the ultrasmall-sized (<0.8 μm) nanohaloarchaea were identified by de novo assembly of metagenomes from hypersaline lakes (lake tyrell, Australia) and halite nodules (Atacama desert) where they appear to thrive under aerobic and hypersaline conditions alongside members of Halobacteria (Ghai et al, 2011;narasingarao et al, 2012;Podell et al, 2013;crits-cristoph et al, 2016).…”
Section: Eukaryotic and Prokaryotic Diversity In Saline Transylvanianmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, Proteobacteria was also the most dominant phylum (Figure a), and a similar situation was found in other studies (Andrei et al, ; Ma et al, ; Shen et al, ; Zhang, Hu, Ren, & Zhang, ; Zhu, Wang, Zhang, Zhu, & Zou, ). However, the total number of bacterial phyla was similar to that in sandy tidal flat (18 phyla), wetland (20 phyla) and early biofilms (11 phyla) (Peng, Li, Lu, Xiao, & Yang, ; Shen et al, ; Zhu et al, ), but less than that in mudflats (53), hypersaline sapropels (59 phyla) and mangrove mudflats (57 phyla) (Ma et al, ; Andrei et al, ; Zhang, Hu, Ren, & Zhang, ), most likely because of the differences in the physicochemical properties and disturbances in the environments. The main reason for these relationships might also be that the organic matter content was lower, and the oxygen content was higher in the sandy tidal flat than in the other mudflat habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the SSU rDNA metabarcoding analysis of environmental samples further suggested that representatives of thirty-two candidate divisions and possibly undocumented prokaryotic lineages might be present in the hypersaline sapropels of both lakes. Among the most abundant MDM members detected were OP1 ('Acetothermia'), OP3 ('Omnitrophica'), OD1 ('Parcubacteria'), WWE1 ('Cloacimonetes') and Parvarchaeota (Andrei et al, 2017). These microbes might be involved in the iron-cycling (Parvarchaeota (Fig.…”
Section: Microbial Diversitymentioning
confidence: 99%